PELAKSANAAN PENDIDIKAN KARAKTER DALAM PEMBELAJARAN PPKN DI KELAS X (SEPULUH) KGSP-B SMK NEGERI 2 SALATIGA - Regi Kristiawan; Nani Mediatati (Jurnal PPKn, 2019)
This study aims to describe the implementation of character education in PPKn learning in class X KGSP B of SMK Negeri 2 Salatiga. Type of research: qualitative descriptive, research subject of PPKn teachers and students. Data collection: unstructured interview techniques, passive observation, documentation, and questionnaires. Data analysis using qualitative analysis. Research results: The implementation of character education in PPKn learning has been carried out starting from the planning, implementation and evaluation stages, the characters that grow: are religious, responsible, honest, disciplined, nationalism, and work together. Obstacles: some students lack character during learning. Solution: do a small reprimand and a friendly approach. PPKn learning is effective in carrying out character education.   Full Paper